Bioactive Compounds of Opuntia spp. Acid Fruits: Micro and Nano-Emulsified Extracts and Applications in Nutraceutical Foods - Fabián Fernández-Luqueño (MDPI AG, 2021)
The acid fruit of the "xoconostle" cactus belongs to the genus Opuntia family of cacti. It is used as a functional food for its bioactive compounds. Several studies reported that xoconostle fruits have a high amount of ascorbic acid, betalains, phenols, tannins, and flavonoids. These compounds confer antioxidant, antibacterial, anti-inflammatory, and hepatoprotective gastroprotective activity. Xoconostle fruit extracts were tested by in vitro assays where the digestion conditions were simulated to measure their stability. At the same time, the extracts were protected by encapsulation (microencapsulation, multiple emulsions, and nanoemulsions). Applications of encapsulated extracts were probed in various food matrices (edible films, meat products, dairy, and fruit coatings). The xoconostle is a natural source of nutraceutical compounds, and the use of this fruit in the new food could help improve consumers’ health.